First detection of the amphibian chytrid fungus (Batrachochytridium dendrobatidis) in free- living anuran populations in Greece - AZMANIS, P. N.; STRACHINIS, I.; LYMBERAKIS, P.; MARSCHANG, R. E. (Journal of the Hellenic Veterinary Medical Society, 2018)
The amphibian chytrid fungus (Batrachochytrium dendrobatidis) is a widespread, cosmopolitan pathogen largely affecting free-living amphibian populations. So far there are no published studies for the presence of B. dendrobatidis in Greece. In this preliminary study we sampled 59 metamorphosed anurans from four Greek wetlands. Five samples were positive for the fungus by real-time PCR. B. dendrobatidis was detected in three species (Bufo viridis, Pelophylax epeiroticus, Pelophylax ridibundus) but not in endangered endemic Karpathos water frogs (Pelophylax cerigensis). This is the first report of the amphibian chytrid fungus (Batrachochytrium dendrobatidis) in free-living anuran populations from Greece.